2014
DOI: 10.1002/2014ja020427
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostics of an artificial relativistic electron beam interacting with the atmosphere

Abstract: We use a Monte Carlo model to simulate the interaction of a beam of relativistic (0.5–10 MeV) electrons with the upper atmosphere as they are injected downward from a notional high‐altitude (thermospheric/ionospheric) injection platform. The beam parameters, defined by realistic parameters of a compact linear accelerator, are used to create a distribution of thousands of electrons. Each electron is injected downward from 300 km altitude toward the dense atmosphere, where it undergoes elastic and inelastic coll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(45 citation statements)
references
References 23 publications
0
45
0
Order By: Relevance
“…Based on these observations and estimations of the source regions, MeV and sub‐MeV electrons can cause an electron aurora simultaneously with the IPA. Marshall et al () simulated optical emissions generated by relativistic electron beam using a Monte Carlo model. The dominant emissions are the first and second positive systems of N 2 and the first negative systems of N2+ in their simulations.…”
Section: Discussionmentioning
confidence: 99%
“…Based on these observations and estimations of the source regions, MeV and sub‐MeV electrons can cause an electron aurora simultaneously with the IPA. Marshall et al () simulated optical emissions generated by relativistic electron beam using a Monte Carlo model. The dominant emissions are the first and second positive systems of N 2 and the first negative systems of N2+ in their simulations.…”
Section: Discussionmentioning
confidence: 99%
“…The EPMC model used here is adapted from the Monte Carlo model of Lehtinen et al (). This model has been used for a variety of purposes in recent years, including calculating the atmospheric effects of an artificial beam of relativistic electrons (Marshall et al, ) and studying the effects of bremsstrahlung propagation into the stratosphere (Xu et al, ).…”
Section: Simulation Proceduresmentioning
confidence: 99%
“…Beam Detectability and Ground-Based Diagnostics Neubert et al (1996), Krause (1998), and Krause et al (1999) demonstrated that relativistic beams injected from the ionosphere into the atmosphere below would produce significant electron-density enhancements, optical emissions, and measureable height-integrated X-ray fluxes. Marshall et al (2014) expanded on the work of Krause (1998) to calculate optical emissions observable from the ground, Xray production and propagation and detectability from satellites and balloons, and backscattered electrons that could be observed from Low Earth Orbit (LEO). That study showed that optical signatures were likely detectable, X-ray fluxes were likely to be far too low from either LEO or balloon altitudes, and ionization could likely be measured form the ground using incoherent scatter radar.…”
Section: Beam Propagationmentioning
confidence: 99%
“…That study investigated a pulse of electrons with 0.05-1 Joules of total energy. Recent accelerator design efforts are targeting a beam total energy of 100-1,000 J, prompting a revisit to the calculations of Marshall et al (2014).…”
Section: Beam Propagationmentioning
confidence: 99%